2023
DOI: 10.1021/acs.chemmater.3c01273
|View full text |Cite
|
Sign up to set email alerts
|

Heteroanionic LaBrVIO4 (VI = Mo, W): Excellence in Both Nonlinear Optical Properties and Photoluminescent Properties

Zixian Jiao,
Osvaldo Medina Mireles,
Kevin Ensz
et al.

Abstract: Five heteroanionic oxybromides, LaBrMoO4, LaBrWO4, (La0.9Sm0.1)BrMoO4, (La0.9Sm0.1)BrWO4, and (La0.9Dy0.1)BrWO4, were grown by a high-temperature salt flux method. Millimeter-sized crystals were collected after salt flux was removed by DI water. The crystal structures were accurately determined by single-crystal X-ray diffraction. LaBrMoO4 is isostructural to LaBrWO4. The substitution of lanthanum for rare earth elements does not change the crystal structure. LaBrWO4 is the first acentric tungsten-containing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 137 publications
1
9
0
Order By: Relevance
“…60 CeBrWO 4 is a new compound, which has never been reported. Like CeBrMoO 4 and CeClMoO 4 , CeBrWO 4 is also isotypic to LaBrWO 4 32 and crystallizes in the acentric monoclinic space group Pc (no. 7) with unit cell parameters of a = 9.8783(1) Å, b = 5.9223(1) Å, c = 7.9394(1) Å, and β = 90.008(1)°.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…60 CeBrWO 4 is a new compound, which has never been reported. Like CeBrMoO 4 and CeClMoO 4 , CeBrWO 4 is also isotypic to LaBrWO 4 32 and crystallizes in the acentric monoclinic space group Pc (no. 7) with unit cell parameters of a = 9.8783(1) Å, b = 5.9223(1) Å, c = 7.9394(1) Å, and β = 90.008(1)°.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous bonding picture study of LaBrWO 4 revealed the moderately strong interaction of the elongated W–O interactions of 2.24 Å. 32 The 2D [CeBrO 4 ] 6− strips are built by distorted tetracapped trigonal prisms [CeO 6 Br 3 ], where six oxygen atoms and three bromine atoms surround the central Ce atoms. The Ce–Br interactions fall into the range of 3.1393(16)–3.257(2) Å, which is similar to many compounds that include Ce–Br interactions such as, CeBr 3 (3.108–3.158 Å), 66 CeBrMoO 4 (3.112–3.227 Å), 60 Ce 3 (SiS 4 ) 2 Br (3.101–3.328 Å), 67 etc .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with centrosymmetric solids, acentric solids draw growing attention from the research community due to the chance of studying directional physical properties such as second harmonic generation, 1–15 nonreciprocal responses, 16–21 etc. From a chemistry perspective, various strategies have proved efficient to influence the creation of a noncentrosymmetric (NCS) structure, including incorporating second order Jahn–Teller distortion 22,23 and conjugated structure motifs such as distorted FeS 4 14,24 or GeS 4 tetrahedra, 25,26 WO 5 , 27 LaO 6 Br 3 , 28 etc. Another systematic way to influence a NCS structure is through incorporating atoms with stereochemically active lone pairs (SCALPs), including Tl + , Sn 2+ , Pb 2+ , As 3+ , Sb 3+ , Bi 3+ , Te 4+ , etc.…”
Section: Introductionmentioning
confidence: 99%